Genogram: a tool for characterizing the families of adolescents parents in João Pessoa, Paraíba State, Brazil = Genograma: ferramenta para caracterizar as famílias de pais adolescentes em João Pessoa, Estado da Paraíba, Brasil - Alice Iana Tavares Leite; Neusa Collet; Sonia Maria Könzgen Meincke; Telma Elisa Carraro; Débora Raquel Soares Guedes Trigueiro (Universidade Estadual de Maringá, 2012)
The study aimed to characterize the family composition of adolescent fathers in the city of João Pessoa, Paraíba State. This is a part of a multicenter survey developed in the states of Paraíba, Rio Grande do Sul and Santa Catarina. The population was composed of ten teenage fathers living in the urban area of João Pessoa. Data collection occurred from December 2008 to October 2010 through semi-structured interview and construction of the genogram and eco-map. Participants' age ranged from 16 to 19 years. They all lived with his partner and most had low education. The unemployed and those with income below one minimum wage indicated the family as the keeper of the home. Most fathers also depended on other family housing, and the amount of people living in the same house ranged from three to seven. Despite the existence of conflicting and/or distant relationships, all respondents reported that seek emotional and financial support in their own family. Fatherhood and motherhood in adolescence had already been experienced by some families. Understanding adolescent parents requires a broader view about composition and family dynamics, a task to be faced by health professionals committed to the care, being the genogram a viable and important tool in this process. O estudo objetiva caracterizar a composição familiar de pais adolescentes em João Pessoa-PB. Trata-se de um recorte de pesquisa multicêntrica desenvolvida na PB, RS e SC. Os sujeitos foram dez pais adolescentes, residentes no perímetro urbano de João Pessoa. A coleta de dados ocorreu de dezembro de 2008 a outubro de 2010, por meio de entrevista semiestruturada e construção do genograma e ecomapa. A idade dos participantes variou de 16 a 19 anos. Todos viviam com a companheira; a maioria apresentava baixa escolarização. Os desempregados e os de renda abaixo de um salário mínimo indicaram a família como mantenedora do lar. A maioria ainda dependia da moradia de outros familiares e a quantidade de pessoas que viviam na mesma casa variou de três a sete. Apesar da existência de relacionamentos conflituosos e/ou distantes, todos os entrevistados relataram buscar apoio emocional e financeiro na própria família. A paternidade e a maternidade na adolescência já haviam sido experienciadas por algumas famílias. Compreender pais adolescentes requer uma visão ampliada acerca da composição e dinâmica familiar, tarefa a ser enfrentada pelos profissionais de saúde comprometidos com o cuidar sendo o genograma uma ferramenta importante e viável nesse processo.